Evaluation of phosphorus-enriched organic amendments to enhance soil phosphorus availability (Zoo Botanica, 2025)
The primary issue confronting the majority of farmers is a lack of phosphorus (P) in soil. A research study involving composting of city waste with organic and inorganic amendments was conducted to assess the impact of these amendments on P availability in soil. Experimental treatments included: City Waste (CW), CW + Single Super Phosphate (SSP), CW + Farmyard Manure (FYM) (EC1) + SSP, CW + Poultry Litter (PL) + SSP (EC2). Two enriched composts were selected based on P content to grow the maize crop under greenhouse conditions to assess the impact of compost on soil and plant growth. Greenhouse experiment consisted of six treatments, viz., control, enriched compost 1 (EC1) @125kg P2O5 /ha, EC2@125kg P2O5 /ha, SSP@125kg P2O5 /ha, ½ EC1+ ½ SSP, ½ EC2+ ½ SSP at recommended rate. Soil samples were analyzed for pH, EC, and macronutrients (N, P, K), before and after crop harvest. Plant samples were also subjected to macro and micronutrient to evaluate the impact of compost on plant nutrient contents. Plant agronomic parameters, viz., plant height, fresh biomass weight, were also recorded Analytical results revealed that application of ½ EC2+ ½SSP (CW+PL+SSP) significantly increased P availability in compost (3.26%), plant (0.69%), and soil (15.5 mgkg-1). Plant height ranged from 149 cm to 172 cm. Addition of enriched compost (EC) showed better results compared to control. Application of ½ EC2+ ½ SSP resulted in an 84.3% increase in plant P (1.4%). This work highlighted that aerobic composting of city waste with PL and SSP had the potential to produce good-quality compost, which could enhance the availability of P in soil and plants.
Keywords: Phosphorus; municipal waste compost; enrichment; Single superphosphate